Some Integral Inequalities for n-Polynomial ζ-Preinvex Functions. (6th January 2021) - Wu, Shanhe; Awan, Muhammad Uzair; Ullah, Muhammad Ubaid; Talib, Sadia; Kashuri, Artion
Abstract : In this paper, we study the properties of n -polynomial ζ -preinvex functions and establish some integral inequalities of Hermite-Hadamard type via this class of convex functions. Moreover, we discuss some special cases which provide a significant complement to the integral estimations of preinvex functions. Applications of the obtained results to the inequalities for special means are also considered.